Oral immunization of mice with a probiotic Lactobacillus casei constitutively expressing the α-toxoid induces protective immunity against Clostridium perfringens α-toxin - Gao, Xuwen; Ma, Yingying; Wang, Zhuo; Bai, Jing; Jia, Shuo; Feng, Baohua; Jiang, Yanping; Cui, Wen; Tang, Lijie; Li, Yijing; Wang, Li; Xu, Yigang (Virulence, 2019)
Clostridium perfringens α-toxin is one of the major virulence factors during C. perfringens infection, causing hemolysis of erythrocytes in various species. Here, genetically engineered Lactobacillus casei (pPG-α/L. casei 393) constitutively expressing the toxoid of C. perfringens α-toxin was generated and its immunogenicity in mice for induction of protective immunity against the α-toxin was evaluated via oral immunization. The α-toxoid was constitutively expressed by pPG-α/L. casei 393 without a specific inducer, as confirmed by western blotting, laser confocal microscopy, and flow cytometry. In an experiment on BALB/c mice to evaluate the oral immunogenicity of pPG-α/L. casei 393, significant levels of a specific secretory IgA (sIgA) antibody in the intestinal mucus and feces and an IgG antibody in the serum of the probiotic vaccine group were detected after booster immunization (p < 0.05) as compared with the pPG/L. casei 393 and PBS control groups. These antibodies effectively neutralized C. perfringens natural α-toxin. Moreover, significantly higher levels of cytokines IL-2, IL-4, IL-10, IL-12, IL-17, and interferon (IFN) γ in the serum and increased proliferation of spleen lymphocytes obtained from mice orally immunized with pPG-α/L. casei 393 were detected. With a commercial C. perfringens type A inactivated vaccine as a control, immune protection provided by the probiotic vaccine against C. perfringens α-toxin was evaluated, and 90% and 80% protection rates were observed, respectively. Therefore, strain pPG-α/L. casei 393 effectively elicited mucosal, humoral, and cellular immunity, suggesting that pPG-α/L. casei 393 is a promising candidate for development of a vaccine against C. perfringens α-toxin.